(untitled) (Marketing Journal, 2025)
This article analyzes marketing strategies that enhance product sales on digital marketplaces. The study applies the AIDA, SOSTAC, and STP models to examine how consumer behavior is influenced by visual presentation, brand trust, and social approval. The e ffectiveness of user engagement techniques, personalized offers, KOL/KOC recommendations, and sustainability -based approaches is supported by empirical evidence. Findings demonstrate that integrated marketing strategies play a crucial role in improving the performance of online sales.